An Assessment of Bureaucratic Capacity, Financial Resources and Accountability as Instruments of Effective Policy Implementation - Yaro, Ibrahim (Journal of Social Transformation and Regional Development, 2023)
For employees. It is therefore, recommended that government agencies should take these vital components into consideration so as any nation to record the desired progress and achieve development objectives, its policies must be properly executed. This is based on the fact that implementing government policies irrespective of the sector concerned is very crucial as it promotes accountability, efficiency in service delivery and improves quality. However, for policies to be effectively implemented, certain factors must be taking into consideration. This research assessed some important components of ensuring effective implementation in government bureaucracies as identified by Elmore (1978, 1997). These are bureaucratic capacity, financial resources and accountability. The research used literature review as its map of action, and identified that bureaucratic capacity could be assessed through professionalism, merit recruitment and diffusion of power. Financial resources on the other hand, could be assessed through performance based pay, cost benefit analysis and fiscal discipline. While accountability depends on the commitments of individual to have effectiveness and efficiency in implementing government policies.